ANALISIS TERHADAP PUTUSAN HAKIM NOMOR 534/PDT.G/2013/PA.PBR.PADA PERKARA CERAI GUGAT OLEH PEGAWAI NEGERI SIPIL DI PENGADILAN AGAMA PEKANBARU - YENI FEBRIZA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
According to Article 1 of Law No. 1 of 1974 on Marriage, marriage is the emotional and physical bond between a man and a woman as husband and wife with the intention of forming a family (household) are happy and eternal berdadasarkan Belief in God Almighty. Marriage is a sacred bond that is also associated with the faith and belief in God. So it is not based on one's desire, but there is a dimension of worship in a marriage. Thus marriage should be maintained properly so what is the purpose of marriage in Islam that is the realization of a prosperous family (sakinah, mawaddah, warahmah) can be realized. Pekanbaru City Region which incidentally have enough qualified civil servants in the government sector is irony to be one area that the divorce rate sufficient to increase every year in the jurisdiction of religious courts Pekanbaru. Class 1 A religious court Pekanbaru as a research done, the courts that are within the judicial power in the judiciary menaganani divorce cases, including contested divorce cases, both contested divorce or divorce from the usual accountability among civil servants. Based on the above settings should any civil servant who wants to file a divorce was required to obtain permission from the supervisor or the competent authority, but in practice the civil divorce case is still there that did not get permission from the authorities but still be processed until the verdict as was the case Judgment in case No. 534/Pdt.G/2013/PA.Pbr.Based on the background above, the writer wants to know What are the reasons for divorce in the decision contested by the plaintiff No. Is 534/Pdt.G/2013/PA.Pbr and basic considerations in the decision of the judge that it meets the principle of legal certainty.This type of research when viewed from the angle of its kind, this research can be classified to normative research. Normative research is legal research library that includes the study of the principles of law, the source of the data used is primary data and secondary data, data collection techniques in this study with the literature study and interviews.From the results of research and analysis by the author of the first known principle of legal certainty, the reasons in case Number 534/Pdt.G/2013/PA.Pbr is already in accordance with the legal and regulatory basis there although there are some basic laws that have not been detailed. Second, divorce cases contested by civil servants annually increased and many are yet to get permission from the boss after the due date but still be processed, with the consideration of the judges wanted to bring more benefit than harm because it brings because marriage can no longer be sustained and the plaintiff is willing to make waiver will accept all the risk of not getting permission from his superiors rejection is accompanied by a letter from the officer in this case the judge considers it already meets the mandatory rule of law replaces the existing license for civil servants who want to sue for divorce.Keywords : Analysis - Divorce Sues - Civil Servants